Self-reported side effects of COVID-19 vaccines among the public - Mahmathi, Karuppannan; Long, Chiau Ming *; Mohd Shahezwan, Abdul Wahab; Zakiah, Mohd Noordin; Yee, Shermaine; Hermansyah, Andi (Taylor and Francis Group, 2024)
Background: The safety, side effects and efficacy profile of COVID-19 vaccines remain subjects of ongoing concern among the public in Malaysia. The aim of this study was to determine the types of adverse effects following immunisation with COVID-19 vaccines and the differences based on various types of COVID-19 vaccines to raise public awareness and reduce vaccine hesitancy among the public.